Strategi Peningkatan Kesempatan Kerja Berbasis Potensi Wilayah: Evaluasi Tenaga Kerja Mandiri Pemula - Yuliastuti, Ari (Journal of Social Movements, 2024)
Unemployment is a common social phenomenon in third-world countries, including Indonesia, which has an abundant workforce. One type of unemployment to note is open unemployment, which includes individuals who are unemployed and are looking for work or those who are preparing for independent enterprise. This phenomenon has a significant impact on the economic and social dynamics of a country. This study aims to evaluate the beginner Independent Workforce (TKM) program as part of efforts to expand employment opportunities in Indonesia. The CIPP evaluation method (Context, Input, Process, and Product) was used to thoroughly review this program. Data was collected through in-depth interviews, FGDs, and literature reviews, involving TKM recipients in several regions. The evaluation results show that the novice TKM program faces several obstacles, such as improper selection of business types, short periods of assistance, and poorly targeted selection of beneficiaries. The fast selection process also makes it difficult for business sustainability. The Bizhub system, which often experiences technical problems, also hinders beneficiaries' access. The study concluded that improvements need to be made in the design and implementation of the beginner TKM program, including increased clarity in the selection of business types, extension of the program period, and more mature selection of beneficiaries. More effective assistance and improvements to the administrative system are also needed to ensure the success of the program. Thus, the beginner TKM-based job opportunity expansion program can be more effective in supporting the growth of independent businesses and reducing unemployment in Indonesia.